IV Paracetamol for closure of patent ductus arteriosus in preterm neonates admitted to a tertiary care centre - B., Sunil; Patel, Shruthi; N., Girish (International Journal of Contemporary Pediatrics, 2018)
Background: Ductus arteriosus is a vascular connection between the pulmonary artery and descending aorta. The incidence is inversely related to birth weight and gestational age (GA). In preterm infants it varies between 40% and 60% on the third day of life. At present, the choice of treatment of clinically significant PDA is with either ibuprofen or indomethacin, but they carry many contraindications and potential side effects. Hence it is important to consider that paracetamol may be used as an alternative to other non steroidal anti-inflammatory drugs and is effective in ductal closure with minimal side effects. Methods:Thirty six preterm infants with hemodynamically significant PDA(hs-PDA) were treated with intravenous paracetamol and subsequent closure was evaluated clinically and by follow-up 2D-Echo. Results: PDA closure following intravenous paracetamol was evident in 27 babies (75%). There were no significant side effects noted with paracetamol therapy. Conclusions: This study shows that paracetamol could offer favourable safety profile in comparison to current treatment options. Therefore, paracetamol may be accepted as a first-line drug treatment for PDA in preterm infants.